The treasured giants: a current overview on agricultural, nutritional, bioactive, and economic potential of Macrocybe Species (Agaricales, Basidiomycota) - Peiris, Thivanka M.; Perera, Menasha; Munasinghe, Helani H.; Thambugala, Kasun M.; Dharmasena, Buddhika P.; Suttiprapan, Piyawan; Cheewangkoon, Ratchadawan (Frontiers in Cellular and Infection Microbiology, 2024)
Macrocybe is a well-studied genus in the family Callistosporiaceae (Basidiomycota). Currently, the genus comprises eight species with worldwide distribution. All species in this genus are relatively large compared to other edible mushrooms and are commonly consumed by locals. Cultivation methodologies have been developed for several species of the genus, including M. gigantea, M. crassa, M. titans, and M. lobayensis. These mushrooms can be cultivated in lignocellulosic wastes such as sawdust, straw, and other agro-industrial wastes. The nutritional compositions have been identified for M. gigantea, M. crassa, and M. lobayensis, revealing that they are rich in fibers, proteins, and various vitamins. Although these mushrooms are of culinary significance, precautions should be taken when consuming them due to their potential cyanic toxicity. In addition to being rich in different nutrients, Macrocybe species possess medicinal properties such as antimicrobial, antioxidant, immunomodulatory, anticancer, anti-inflammatory, hepatoprotective, and several other beneficial effects. Several species are commercially available in countries like China and Thailand, and the commercial potential is high due to the large size, taste, and long shelf life of these mushrooms. There is significant potential for cultivating species of this genus and introducing their artificial cultivation practices to various counties worldwide. Diverse value-added products can also be produced using Macrocybe species.